PERAN GURU PENDIDIKAN JASMANI DALAM MEMBENTUK KARAKTER SISWA PADA MA. SEDESA MERTAKTOMBOK TAHUN PELAJARAN 2020/2021 - Wahyudi, Johan; Mus'id, Rodinal (LPPM Institut Pendidikan Nusantara Global, 2020)
This research entitled was “The Role of Physical Education Teachers in shaping the character of students in MA. In the whole village of Mertak Tombok”. This research aims to determine the role of physical education teachers in shaping the character of MA students. In the whole village of Mertak Tombok. The type of research was descriptive research with a qualitative approach. The population in this research was all physical education teachers in MA. in village of Mertak Tombok, totaling 5 people. Sampling was done by total sampling technique. So the samples in this research were all physical education teachers who were in MA. The village of Mertak Tombok, totaling 4 people. The data was collected using a questionnaire. The data obtained was processed using statistical techniques. The village of Mertak Tombok for the 2020/2021 academic year so that it can shape the character of students for the better. It is recommended that prospective physical education teachers who become a teacher really have to carry out their duties as professional teachers who are active and creative in nurturing students so that they become a generation of people who have good characters that are beneficial to the nation and state.